The roles of language and executive function in Mandarin-speaking children’s theory of mind development - Li, Honglan; Leung, Man-Tak (Frontiers in Psychology, 2024)
Research has indicated that language and executive function relate closely to first-order false belief reasoning, yet their roles in second-order false belief reasoning are under-explored, and their interplay in theory of mind development remains obscure. This study assessed 160 Mandarin-speaking preschoolers' and early primary schoolers' language, executive function, and theory of mind abilities to examine the unique roles and interplay of language and executive function in first-order and second-order false belief reasoning. Results showed that language significantly uniquely predicted the children's first-order as well as second-order false belief reasoning when controlling for the effects of age and executive function. Although executive function significantly predicted first-order FB reasoning when controlling for age, it was no longer a significant predictor of first-order FB reasoning when language was included in the model. However, executive function played a significant unique role in second-order FB reasoning when controlling for the effects of age and language. The current findings suggest that language plays a greater role than executive function in Mandarin-speaking children's theory of mind development and the contributors to theory of mind development vary in different levels of false belief reasoning.